2008
DOI: 10.1182/blood.v112.11.871.871
|View full text |Cite
|
Sign up to set email alerts
|

Vorinostat Plus Bortezomib for the Treatment of Relapsed/Refractory Multiple Myeloma: Early Clinical Experience

Abstract: Bortezomib, a proteasome inhibitor, is extremely effective for the treatment of multiple myeloma (MM). However, nearly all patients will eventually become refractory to bortezomib. Vorinostat is a potent inhibitor of histone deacetylase enzymes, and has been shown to affect growth of various cell lines, including MM, in a variety of in vitro non-clinical studies. Furthermore, the combination of bortezomib and vorinostat has demonstrated synergy in several in vitro and murine models. Subsequently, 2 multicenter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…In support of these effective combination therapies, the activity of vorinostat combined with bortezomib has previously been demonstrated in preclinical and clinical studies (29–33), and shown to enhance the antimyeloma activity of other anticancer agents including tumor necrosis factor‐related apoptosis‐inducing ligand, and interferon α2b (34, 35). Furthermore, other HDAC inhibitors have also shown the ability to enhance the activity of bortezomib and melphalan in chemoresistant myeloma cells.…”
Section: Discussionmentioning
confidence: 99%
“…In support of these effective combination therapies, the activity of vorinostat combined with bortezomib has previously been demonstrated in preclinical and clinical studies (29–33), and shown to enhance the antimyeloma activity of other anticancer agents including tumor necrosis factor‐related apoptosis‐inducing ligand, and interferon α2b (34, 35). Furthermore, other HDAC inhibitors have also shown the ability to enhance the activity of bortezomib and melphalan in chemoresistant myeloma cells.…”
Section: Discussionmentioning
confidence: 99%
“…[97]. In addition, earlyphase clinical trials of vorinostat in patients suffering from multiple myeloma demonstrated an increase in its antitumor effects in combinations with bortezomib [98][99][100]. Mitochondrial damage, stimulations of JNK and caspases or enhanced oxidative stress were increased in cells exposed to proteasome and HDAC inhibitors used in combination.…”
Section: Hdac Inhibitors and Other Therapeutic Regimensmentioning
confidence: 99%
“…33,94 The transcriptional and protein homeostasis effects of HDAC inhibitors could conceivably cooperate to enhance the anti-MM activity of bortezomib, including clinical responses even in bortezomib-refractory patients. 28,91 The combination of elotuzumab with lenalidomide was made based on the notion that the immunostimulatory effect of lenalidomide would enhance the antibodydependent cellular cytotoxicity triggered by elotuzumab.…”
Section: Role Of Combination Regimens In the Future Of MM Treatmentmentioning
confidence: 99%